Similaridade dos principais assuntos de auditoria em companhias abertas brasileiras - Otávio Araújo de Carvalho (2021)
The Key Audit Matters (KAMs) were introduced in Brazil as of 2016, with the aim of making the audit report more informative and transparent. Studies have shown that these issues are relevant to information users, but the fear arose that these KAMs would lose informational value due to repetition over the years. This research aimed to identify the determinants for similarity of KAMs in publicly traded companies traded on B3. A sample of 309 companies traded on B3 in the period from 2016 to 2019 was used, composing an unbalanced panel of 836 observations. The average similarity index of KAMs in the analyzed period was 69.13%. By performing average tests, the existence of a difference in the KAMs similarity index between auditing firms and economic sectors was verified. The results estimated by the Generalized Least Squares (GLS) method showed that the rotation of the audit firm and the size of the audited company have a negative influence on the similarity of the KAMs. This research helps information users and independent auditors understand factors that may influence the similarity in the disclosure of KAMs, as well as for regulatory bodies to assess the factors that impact the similarity of KAMs and verify whether the objective of bringing a new, more informative, transparent and non-standardized audit report is being achieved. This work also contributes to academia, as it presents the KAMs similarity index, the characteristics of audit firms and companies that affect this index, and the existing differences in the similarity of these issues between economic sectors and auditing firms.